Understanding Multiferroic Hexagonal Manganites by Static and Ultrafast Optical Spectroscopy - Yu Ting Wang; Chih Wei Luo; Takayoshi Kobayashi (Advances in Condensed Matter Physics)
Multiferroic hexagonal manganites ReMnO3 studied by optics are reviewed. Their electronic structures were revealed by static linear and nonlinear spectra. Two transitions located at ~1.7 eV and ~2.3 eV have been observed and attributed to the interband transitions from the lower-lying Mn3+dxy/dx2-y2 and dxz/dyz states to the Mn3+d3z2-r2 state, respectively. These so-called d-d transitions exhibit a blueshift as decreasing temperatures and an extra blueshift near TN. This dramatic change indicates that the magnetic ordering seriously influences the electronic structure. On the other hand, the ultrafast optical pump-probe spectroscopy has provided the important information on spin-charge coupling and spin-lattice coupling. Because of the strongly correlation between electronic structure and magnetic ordering, the amplitude of the initial rising component in ΔR/R shows striking changes at the vicinity of TN. Moreover, the coherent optical and acoustic phonons were observed on optical pump-probe spectroscopy. Both the amplitude and dephasing time of coherent phonons also exhibit significant changes at TN, which provide the evidence for spin-lattice interaction in these intriguing materials.